Cerebrospinal fluid analysis and changes over time in patients with subarachnoid hemorrhage: a prospective observational study - Alessandro Pesaresi; Denise Battaglini; Pasquale Anania; Silvia Sgambetterra; Camilla Origlia; Gianluigi Zona; Thomas Langer; Nicolò Antonino Patroniti; Pietro Fiaschi; Chiara Robba (Journal of Anesthesia, Analgesia and Critical Care)
Abstract Background Changes in cerebrospinal fluid (CSF) in patients with aneurysmal subarachnoid hemorrhage (aSAH) have not been fully elucidated, yet they are critical and may potentially be associated with the risk of complications. The aim of this study is to characterize the biochemical properties of CSF and examine the temporal changes in aSAH patients with and without post-aSAH complications such as vasospasm and shunt-dependent hydrocephalus. Methods This prospective observational longitudinal cohort study involved collecting CSF and arterial blood samples from SAH patients requiring an external ventricular drain at four different timepoints following the initial event (1–3, 4–7, 8–13, and 14–20 days after aSAH). A control group that comprised patients with idiopathic normal pressure hydrocephalus undergoing CSF sampling was included. Results A total of 20 SAH patients and 20 controls were enrolled. We observed significantly higher levels of hemoglobin (Hb), proteins, lactate, and cell concentrations in the CSF of aSAH patients compared to the control group (p < 0.001), with no corresponding differences in serum levels. Furthermore, a progressive decline in CSF Hb, proteins, and cells levels was noted over the days following the hemorrhage (p = 0.029, p = 0.005, and p = 0.010, respectively). Patients that developed vasospasm exhibited a lower CSF glucose/lactate ratio (p < 0.001) and reduced CSF sodium levels (p = 0.045), while patients that developed shunt-dependent hydrocephalus exhibited higher plasmatic and CSF glucose levels (p = 0.013 and p = 0.003, respectively) and lower CSF Hb/proteins ratio (p < 0.001). Conclusions Patients with aSAH exhibit changes in the biochemical profile of the CSF, which evolve over time following the acute event. Parameters such as CSF glucose/lactate ratio and CSF Hb/proteins ratio could potentially provide valuable insights not only into the pathophysiology of aSAH but also into patient risks of post-hemorrhagic complications, such as vasospasm and hydrocephalus.